The Manifestation of Entrepreneurial Orientation in the Social Entrepreneurship Context. Issue 3 (2nd September 2019) - Alarifi, Ghadah; Robson, Paul; Kromidha, Endrit
Abstract: This study extends theorisation of entrepreneurial orientation (EO) in the social entrepreneurship context by introducing firm performance as a construct for examining social enterprises (SEs) EO. Drawing on EO and firm performance research indicating that EO is related to a better firm performance, this paper argues that EO in SEs is positively related to organisational performance. This research empirically studies 303 social enterprises in Saudi Arabia and develops three hypotheses that examine the relationship between entrepreneurial orientation (EO) and social entrepreneurs' firm performance. The results show that innovativeness and proactiveness, but not risk-taking, are positively associated with firm performance. Thus, whilst SEs cover a wide range of business activities there is generally a positive effect of EO across the contexts investigated. Also, this research found that EO can be used as a mechanism to overcome constraints imposed by limited resources in an environment where new opportunities rarely occur.